Comparative Analysis of Soil Microbiome Profiles in the Companion Planting of White Clover and Orchard Grass Using 16S rRNA Gene Sequencing Data - Chen, Lijuan; Li, Daojie; Shao, Ye; Adni, Jannati; Wang, Hui; Liu, Yuqing; Zhang, Yunhua (Frontiers in Plant Science, 2020)
Companion planting is one of the most common and effective planting methods in modern agriculture. White clover (Trifolium repens L.) and orchard grass (Dactylis glomerata L.) are two typical pastures planted together to promote each other’s growth. However, the detailed biological foundations of companion planting remain unclear. In this study, we screened typical microbiome profiles under separate and combination planting conditions using 16s RNA sequencing techniques. We identified the typical distinctive microorganism subtypes based on the microbiome profiles and recognized the enriched functions of top abundant microorganisms in soil using different planting strategies with the help of Kyoto Encyclopediaa of Genes and Genomes and Clusters of Orthologous Groups annotation. This analysis confirmed that the optimal microorganisms and screened functional annotations are correlated with nitrogen fixation; thus, companion planting may improve the yield and efficacy of plants by improving the efficiency of nitrogen fixation.